Empowering single mothers in Selangor : a community-based intervention programme - Halimaatun Syakirah Omar (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims at developing a community-based intervention programme for single mothers in Selangor using a health empowerment model to examine its effectiveness. The programme focused on three areas namely building personal resources, recognising social contextual resources and utilising social services. It was a five-week intervention programme with 2.5 hours per session. Using a non-randomised experimental design, 12 single mothers made up the intervention group while eight single mothers served as the control group (Group). The effectiveness of this intervention programme was assessed using five well-being measures – mental health, self-efficacy, community engagement, social support and religiosity – through self-report questionnaires that were administered before and after the intervention programme (Time). For the intervention group, an interview was conducted to provide additional information on the effectiveness of the programme. A 2 x 2 analysis of variance (ANOVA) was used with Time as the within subject factor and Group as the between-subject variable. Results show significant main effect of Time for self-efficacy, community engagement, social support and religiosity. Most importantly, the result revealed significant Group x Time interaction for self-efficacy. The participants in the intervention group reported a significant change in scores of self-efficacy after the intervention programme compared to the control group. The data obtained from the interviews further substantiated the quantitative results. The implications of this study were discussed.